2018
DOI: 10.25121/ns.2018.23.4.153
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management of root-fractured primary incisor – case report

Abstract: Most frequent trauma to primary dentitions are injures to the supporting tissue i.e. luxations, but root fractures are relatively uncommon. The difference in the trauma pattern favoring luxation rather than fracture has been found to be typical for the primary dentition, since the elasticity of the alveolar bone surrounding the primary teeth is high and primary tooth held in alveolar socket is less strong. Incidence of foot fractures increases at the age of 3-4 years where physiologic root resorption has begun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…This report is based on eight years of clinical and radiographic reviews, which showed spontaneous healing of the traumatized tooth and normal eruption of the permanent successor. Traumatic dental injuries such as horizontal root fractures are rare in the primary dentition and they may be a challenge for clinicians as they usually remain asymptomatic 16 . Their incidence increases at the age of 3–4 years due to the beginning of physiologic root resorption which weakens the root 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This report is based on eight years of clinical and radiographic reviews, which showed spontaneous healing of the traumatized tooth and normal eruption of the permanent successor. Traumatic dental injuries such as horizontal root fractures are rare in the primary dentition and they may be a challenge for clinicians as they usually remain asymptomatic 16 . Their incidence increases at the age of 3–4 years due to the beginning of physiologic root resorption which weakens the root 17 .…”
Section: Discussionmentioning
confidence: 99%
“…such as horizontal root fractures are rare in the primary dentition and they may be a challenge for clinicians as they usually remain asymptomatic. 16 Their incidence increases at the age of 3-4 years due to the beginning of physiologic root resorption which weakens the root. 17 They are generally located in the middle or apical third of the root, with radiolucent lines separating the fragments.…”
Section: A S E Rep Ortmentioning
confidence: 99%
“…Mobility was reported in four cases; specifically, this was of grade II in the two cases described by Kumari et al [28] and in the case of Liu et al [18]. Mobility was also highlighted by Brudza-Zwiech et al in their root fracture case, but this time without specifying the degree [29]. Regarding dental luxation trauma, Bonanato et al described a case with an extrusive vestibular luxation [14], Liu et al [18] described a 1 mm palatal extrusive luxation, and Di Giorgio et al noted a 3 mm one [30].…”
Section: Further Trauma And/or Dislocation Sufferedmentioning
confidence: 92%
“…In the case reports, six fractures lines were in the apical third [14,18,[27][28][29][30], and three in the middle third [18,28,32]. As for the 53 teeth of the retrospective study, Cho et al did not specify the exact location of the fracture, but wrote that all were fractures affecting the apex or the middle third of the root [31].…”
Section: Type Of Root Fracturementioning
confidence: 99%
See 1 more Smart Citation